2021
DOI: 10.1039/d1ta03718h
|View full text |Cite
|
Sign up to set email alerts
|

The crucial roles of the configurations and electronic properties of organic hole-transporting molecules to the photovoltaic performance of perovskite solar cells

Abstract: Perovskite solar cells have become one of the most promising technologies to make use of solar energy, the power conversion efficiences (PCEs) have been improved from 3.8% to 25.6% until...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 141 publications
0
27
0
Order By: Relevance
“…The results show that the annealing duration of CMT leads to different HTL film morphologies, and the smoother surface can benefit the perovskite to crystallize with a bigger grain size, which may result in better hole extraction and device performance (higher V OC and FF). 36 After optimization, the highest PCE obtained is 20.4% for dopant-free CMT-based p-i-n pero-SCs, which is much higher than 13.05% for CMT-based n-i-p pero-SCs and among the PCEs of the FMT-and DBFMT-based p-i-n pero-SCs (Figure 6a and Table 1). The external quantum efficiency (EQE, Figure 6b) has been investigated to calculate the J SC , and the J SC obtained from the J−V test for the best dopant-free CMTbased device (23.27 mA/cm 2 ) is in accord with the integrated one (22.35 mA/cm 2 ) within a 4% deviation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The results show that the annealing duration of CMT leads to different HTL film morphologies, and the smoother surface can benefit the perovskite to crystallize with a bigger grain size, which may result in better hole extraction and device performance (higher V OC and FF). 36 After optimization, the highest PCE obtained is 20.4% for dopant-free CMT-based p-i-n pero-SCs, which is much higher than 13.05% for CMT-based n-i-p pero-SCs and among the PCEs of the FMT-and DBFMT-based p-i-n pero-SCs (Figure 6a and Table 1). The external quantum efficiency (EQE, Figure 6b) has been investigated to calculate the J SC , and the J SC obtained from the J−V test for the best dopant-free CMTbased device (23.27 mA/cm 2 ) is in accord with the integrated one (22.35 mA/cm 2 ) within a 4% deviation.…”
Section: Resultsmentioning
confidence: 93%
“…As CMT is annealed at 100 °C for 5 and 10 min, the RMS value decreases to 0.38 nm and 0.42 nm, respectively. The results show that the annealing duration of CMT leads to different HTL film morphologies, and the smoother surface can benefit the perovskite to crystallize with a bigger grain size, which may result in better hole extraction and device performance (higher V OC and FF ) …”
Section: Resultsmentioning
confidence: 99%
“…Among all the four HTMs, the highest mobility of FMT-D may originate from the stronger molecular interaction and the smoother surface in the film states when increasing the length of the chain, which may improve the fill factor (FF) of the pero-SCs. 8 To explore the impact of FMT-M, FMT-EH, FMT, and FMT-D on the crystallization of the top perovskite films, we compared the X-ray diffraction (XRD) patterns of perovskite films on the surface of different HTLs. It can be observed that the intensities of the (110) diffraction peak at 2θ of 14.2°for the perovskite films on top of FMT and FMT-D are stronger than the ones on top of FMT-M, FMT-EH, and ITO (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…The much more planar structure of the molecules may induce tighter molecular packing, shorter intermolecular distance, and higher hole mobility. 35 From the electronic density distribution diagram, it can be noted that the LUMOs (the lowest unoccupied molecular orbitals) of these molecules mainly distribute on the thiophene core and the adjacent units. As for the HOMOs (the highest occupied molecular orbitals), the molecules without double bonds locate on the entire skeleton, while the molecules containing double bonds distribute mainly on the thiophene core and the adjacent units, just like their LUMO distributions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the oxygen-containing molecules display distinctly better planarity by comparison with sulfur-containing molecules. The much more planar structure of the molecules may induce tighter molecular packing, shorter intermolecular distance, and higher hole mobility . From the electronic density distribution diagram, it can be noted that the LUMOs (the lowest unoccupied molecular orbitals) of these molecules mainly distribute on the thiophene core and the adjacent units.…”
Section: Resultsmentioning
confidence: 99%